PELATIHAN PEMANFAATAN ALAT PERAGA BAGI GURU SD MUHAMMADIYAH DI SUKOHARJO DALAM MENGHADAPI ERA REVOLUSI INDUSTRI 4.0 - Fuad Anwar; Kusumandari Kusumandari; Yofentina Iriani; Mohtar Yunianto (Adi Widya : Jurnal Pengabdian Masyarakat, 2020)
Community service activities for Muhammadiyah Elementary School Teachers in Polokarto Subdistrict, Sukoharjo Regency have been carried out. The background of this activity is the information obtained that the teachers in the school still use books and blackboards especially for subjects related to Science so that students become less creative and innovative thinking. activities carried out in the form of ongoing activities, namely training in the use of props style, motion and energy as many as 10 kits, presentation of the results of the practice of using props and the process of dissemination to students. The results obtained that all participants in understanding the teaching aids that have been trained, seen from the activeness of the participants, the ability of participants in the presentation and the results of dissemination to students in their respective schools